2023
DOI: 10.1029/2022sw003349
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric Temperature and Density Variability During 3–4 February 2022 Minor Geomagnetic Storm

Abstract: The Thermosphere-Ionosphere (TI) system of the Earth is externally forced by waves from the lower atmosphere and energy and momentum inputs from the sun through solar irradiance and solar wind energetic particles. The solar irradiance controls the thermospheric background neutral density and temperature through heating by the extreme ultraviolet radiation, one form of solar forcing. Another form of solar forcing comes from solar energetic charged particles from coronal mass ejection, high-speed streams, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…There is another global response of the thermospheric neutral density on the 4th, including an equatorward motion of density enhancements from high northern and southern latitudes over the course of the day, most apparent in the GRACE-FO measurements. This motion is consistent with TAD propagation, and modeling of the same event (Laskar et al, 2023;Lin et al, 2022). Overall, thermospheric densities were significantly higher within the latitude bounds of the initial Starlink orbit (horizontal dashed lines in Figure 1) on the 4th, compared to the 3rd.…”
Section: Thermospheric Density Response and Decaysupporting
confidence: 79%
“…There is another global response of the thermospheric neutral density on the 4th, including an equatorward motion of density enhancements from high northern and southern latitudes over the course of the day, most apparent in the GRACE-FO measurements. This motion is consistent with TAD propagation, and modeling of the same event (Laskar et al, 2023;Lin et al, 2022). Overall, thermospheric densities were significantly higher within the latitude bounds of the initial Starlink orbit (horizontal dashed lines in Figure 1) on the 4th, compared to the 3rd.…”
Section: Thermospheric Density Response and Decaysupporting
confidence: 79%
“…This storm should be considered as a "moderate" storm based on the Dst index (Borovsky & Shprits, 2017;Loewe & Prölss, 1997). The Dst index is not always a great indicator of geomagnetic storms (Borovsky & Shprits, 2017;McPherron & Chu, 2016), thus Laskar et al (2023) also used 3 hourly Kp and Ap indices and National Oceanic and Atmospheric Administration's (NOAA) Space Weather Prediction Center (SWPC) classification during this storm. The maxima of 3-hourly Kp and Ap indices in this storm were 5 + and 56 nT, respectively, thus this storm was classified as a minor storm (G1) according to the NOAA SWPC's Space Weather Scale (https://www.swpc.noaa.gov/noaa-scales-explanation).…”
mentioning
confidence: 99%
“…To gain a better understanding of the thermospheric variations during this minor storm, several studies have been conducted using observations from satellites and numerical simulations from thermospheric models (Cai et al, 2023(Cai et al, , 2024Dang et al, 2022;Fang et al, 2022;Kataoka et al, 2022;Laskar et al, 2023;Lin et al, 2022;Zhang et al, 2022). Dang et al (2022) provided a comprehensive review of the SpaceX event and simulations by the TIE-GCM model showed around 20%-30% atmospheric density perturbations at 210 km during the minor storm.…”
mentioning
confidence: 99%
See 2 more Smart Citations